The influence of the diagnosis of autism on the professional path of the mothers of Florianópolis (Research, Society and Development, 2021)
Women who become mothers and are faced with their children's autism diagnosis, have to adapt life to a new reality. Within this change, the subject of professional career is included, in which they may or may not interrupt it or even change it depending on the situation. Given the above, the objective of this study was to understand the influence of the child's autism diagnosis on the professional trajectory of mothers belonging to the Greater Florianópolis region. Regarding the methodology, it is reported that it was an applied, exploratory and quantitative study. As a data collection strategy, a questionnaire with 76 questions was used, which was sent to 379 mothers of autistic children. The contingent of respondents was compatible with the minimum projected sample. The results showed the profiles and changes that occurred after receiving the children's diagnosis, which, in the end, allowed the identification of similarities and disparities in the professional trajectories of these women, which allowed them to understand their choices.